Transfer of Problem Solving Skills from Touchscreen to 3D Model by 3- to 6-Year-Olds - Tarasuik, Joanne; Demaria, Ana; Kaufman, Jordy (Frontiers in Psychology, 2017)
Although much published research purports that young children struggle to solve problems from screen-based media and to transfer learning from a virtual to a physical modality, Huber et al. (2016)’s recent study on children solving the Tower of Hanoi problem on a touchscreen app offers a clear counter example. Huber et al. reported that children transferred learning from media to the physical world. As this finding arguably differs from that of prior research in this area, the current study tests whether the Huber et al results could be replicated. Additionally, we extended the scope of the Huber et al work by testing a broader age range, including children as young as 3 years, and using a culturally distinct participant pool. The results of the current study verified Huber et al.’s conclusion that 4- to 6-year old children are capable of transferring the Tower of Hanoi learning from touchscreen devices to the physical version of the puzzle. Children under 4 years of age, in contrast, showed little ability to improve at the Tower of Hanoi problem regardless of the practice modality—suggesting that a different problem-solving task is required to probe very young children’s ability to learn from touchscreen apps.